Regulation of the tricarboxylic acid cycle in gram-positive, facultatively anaerobic bacilli. - Tanaka, N (1975)
The facultative anaerobes Bacillus polymyxa Hino G, B. polymyxa Hino J, and B.macerans were observed to have imcomplete tricarboxylic acid cycles. They were devoid of malate dehydrogenase and all had very low levels of alpha-ketoglutarate dehydrogenase. B. polymyxa Hino J was devoid of alpha-ketoglutarate dehydrogenase when grown aerobically and anerobically. Citrate synthase from B. polymyxa was inhibited by adenosine triphosphate but not reduced nicotinamide adenine dinucleotide and resembled enzymes from other gram-positive bacteria in this respect. Like the citrate synthases from gram-negative, facultative anaerobes and chemolithotrophs, the enzyme from B. polymyxa was inhibited by alpha-ketoglutarate. Inhibition by adenosine triphosphate was shown to be competitive with acetyl-coenzyme A and alpha-ketoglutarate inhibition was competitive with oxaloacetate.